Ecology in politics: a multimodal eco-critical analysis of environmental discourse - Al Shazly Amany; Sherif Lubna A. (Language and Semiotic Studies, 2025)
The Grand Ethiopian Renaissance Dam (GERD), established on the Blue Nile, is the largest contemporary hydroelectric power project in Africa. It caused a geopolitical tension between the downstream countries (Egypt and Sudan) and Ethiopia; thus, the various narratives accounting for this environmental issue are worth exploration to promote the understanding of the link between language and the environment. Ecolinguistics is theoretical framework, which addresses pressing ecological issues to promote humans’ understanding of the link between languages and the environment. Thus, the present study investigates the Facebook posts of the official accounts of the Ethiopian Prime Minister, the Egyptian Ministry of Foreign Affairs, and the Egyptian Cabinet to identify the different framings of the GERD. It reveals the interplay between the different modes of communication through an eclectic framework, which integrates the visual analytical model (Kress & van Leeuwen) to Stibbe’s (2015. Ecolinguistics: Language, ecology and the stories we live by. London & New York: Routledge) ecolinguistic framework. The study concludes that the different framings over the GERD reflect different perceptions on environmental discourse, which promote constructive discourse on the management of water resources.